IMPLEMENTATION OF LEARNING INNOVATIONS IN ISLAMIC EDUCATION IN IMPROVING STUDENT ACHIEVEMENT (Study at Shalahuddiin High School In Gayo Lues Regency) - Rodhi Hartono (FITRAH: International Islamic Education Journal, 2019)
Abstract This study is motivated by the fact that the school as an institution directed to create a whole person, not only has a function as an educational institution that is merely formality, but more than that, schools are required to play its function in developing all the potentials and competencies which consist of knowledge, skills and basic values ​​that are reflected in the habits of thinking and acting. Such statements certainly require new findings (read: innovation) in various ways, such as curriculum renewal, improvement of the quality of learning, and the effectiveness of learning methods. For this reason, this study reviews the innovation of Islamic education learning in Shalahuddiin High School in Gayo Lues Regency, with a focus on the discussion on, first, the implementation of PAI learning innovations in improving student achievement in Shalahuddin High School in Gayo Lues Regency. Second, the obstacles faced in implementing PAI learning innovations in these institutions. To answer the problem formulation above, a descriptive-qualitative approach is used with data sources extracted through interview, observation and documentation techniques. Through this methodology, it was concluded that learning innovations applied in the Shalahuddiin High School in Gayo Lues Regency include the use of technological advances in learning, such as the use of power points and audio visuals. Another thing that is also done in this institution as a form of innovation in the learning of Islamic education is by providing an assessment that emphasizes the practical aspects and giving quizzes, games and reading Asmaul Husna as a distraction during the learning process takes place. The obstacles of implementing PAI learning innovation. That is, obstacles that arise from the implementation of policies caused by differences in views among policy holders in the High School (SMA) Shalahuddiin Gayo Lues Regency in interpreting what is called learning innovation. In addition, the lack of supporting facilities and infrastructure also becomes an obstacle in the implementation of learning innovations. Keywords: Innovation, Learning, Learning Achievemen Abstrak Penelitian ini dilatarbelakangi oleh kenyataan bahwa sekolah sebagai institusi diarahkan untuk menciptakan manusia seutuhnya, tidak hanya memiliki fungsi sebagai institusi pendidikan yang hanya formalitas, tetapi lebih dari itu, sekolah dituntut untuk memainkan fungsinya dalam mengembangkan semua potensi dan kompetensi yang terdiri dari pengetahuan, keterampilan, dan nilai-nilai dasar yang tercermin dalam kebiasaan berpikir dan bertindak. Pernyataan seperti itu tentu membutuhkan temuan baru (baca: inovasi) dengan berbagai cara, seperti pembaruan kurikulum, peningkatan kualitas pembelajaran, dan efektivitas metode pembelajaran. Untuk alasan ini, penelitian ini meninjau inovasi pembelajaran pendidikan Islam di SMA Shalahuddiin di Kabupaten Gayo Lues, dengan fokus pada diskusi tentang, pertama, implementasi inovasi pembelajaran PAI dalam meningkatkan prestasi siswa di SMA Shalahuddin di Kabupaten Gayo Lues. Kedua, hambatan yang dihadapi dalam mengimplementasikan inovasi pembelajaran PAI di lembaga-lembaga ini. Untuk menjawab rumusan masalah di atas, pendekatan deskriptif-kualitatif digunakan dengan sumber data diekstraksi melalui wawancara, observasi dan teknik dokumentasi. Melalui metodologi ini, disimpulkan bahwa inovasi pembelajaran yang diterapkan di SMA Shalahuddiin di Kabupaten Gayo Lues mencakup penggunaan kemajuan teknologi dalam pembelajaran, seperti penggunaan power point dan audio visual. Hal lain yang juga dilakukan di lembaga ini sebagai bentuk inovasi dalam pembelajaran pendidikan Islam adalah dengan memberikan penilaian yang menekankan pada aspek praktis dan memberikan kuis, permainan dan membaca Asmaul Husna sebagai selingan selama proses pembelajaran berlangsung. Hambatan menerapkan inovasi pembelajaran PAI. Artinya, kendala yang muncul dari implementasi kebijakan disebabkan oleh perbedaan pandangan di antara pemegang kebijakan di SMA Shalahuddiin Kabupaten Gayo Lues dalam mengartikan apa yang disebut inovasi pembelajaran. Selain itu, minimnya sarana dan prasarana pendukung juga menjadi kendala dalam implementasi inovasi pembelajaran. Kata kunci: Inovasi, Pembelajaran, Prestasi Belajar